Research of Embedded GIS Data Management Strategies for Large Capacity - Shi Bei-lei; Fang Kun; Wu Ke-ming; Ye Li-wei (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With the use of data for embedded GIS system continues to increase and the requirement of application for embedded GIS system continues to improve, the quad-tree index algorithms and block classification data organization mode that are currently used to handle large amounts of data reflects a certain limitation. combining the characteristics of embedded GIS data, the author put forward the multi-level data indexing and dynamic data loading ,and realize the data loading when required, and enhance the real-time response speed, solves the limitation on large volume data. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3967